Hermeneutic Foundations of The Socio-Ethical Views of Thinkers of The Timurid Era - Damirovich , Mustayev (Indonesian Journal Publisher, 2025)
This article presents the opinions of our country and foreign scholars on the hermeneutic foundations of the socio-ethical views of the thinkers of the Timurid era. The article examines the theoretical and methodological foundations of studying the socio-ethical views of thinkers from the Timurid era, as well as the hermeneutic basis of their socio-ethical perspectives. It also explores the educational significance of these views in the context of New Uzbekistan. Additionally, the hermeneutic foundations of the socio-ethical views of Timurid-era thinkers are analyzed.